Optimal control of first-order partial differential inclusions in bounded region - Mahmudov, Elimhan N. (Informa UK Limited, 2021)
The paper is devoted to the Lagrange problem in the bounded region for first-order partial differential inclusions (PDIs). For this, using discretisation method and locally adjoint mappings (LAMs),...